The toll of excess mortality in Europe in 2020-2023 - Gerli, Alberto Giovanni; Alicandro, Gianfranco; Pizzato, Margherita; Vecchia, Carlo La (Journal of Health Inequalities, 2025)
This paper summarizes current evidence on excess mortality in Europe from 2020 to 2023, emphasizing the different drivers of excess death rates during the COVID-19 pandemic. The first two years (2020-2021) accounted for a substantial proportion of additional deaths – estimated at approximately 1,000,000 across 29 European countries – largely due to direct SARS-CoV-2 infection and other factors such as hospital resource constraints and deferred medical care. Excess mortality persisted in 2022 and substantially decreased in 2023. Marked regional disparities emerged, with Eastern Europe, parts of Southern Europe, and specific high-density urban areas reporting some of the highest excess mortality, often linked to structural healthcare limitations and lower vaccination uptake. By contrast, Nordic countries experienced lower surges, partly attributable to robust healthcare infrastructure and proactive public health measures: the smallest excess mortality was in Sweden. Older adults bore most of the burden, underscoring the role of demographic vulnerability. Socioeconomic factors, including gross domestic product and healthcare accessibility, further shaped the uneven toll of the pandemic.